LYRICS BY ALISHER NAVOI (American Journal of Interdisciplinary Research and Development, 2023)
In the article, general information about the lyrics of Alisher Navoi, the characteristics of his works, his influence on our national literature and history, the importance of his lyrics in expressing national feelings and the superiority of the poet's Uzbek literature were discussed.